Penerapan Proses Pengolahan Croissant di Pastry & Bakery Section Hotel Ciputra World Surabaya - Achmad Dafid Al Arif; Ita Fatkhur Romadhoni; Andika Kuncoro Widagdo; Lilis Sulandari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to analyze the application of Croissant processing in Pastry & Bakery Section of Ciputra World Hotel Surabaya. This stage starts from weighing the ingredients, mixing the dough, making lamination, cutting the dough, proofing, baking, and serving croisaant. The focus of the research was on the processing stages of lamination formation using single fold 3 times and producing 27 clearly visible thin layers. The research method involved observation, interview, and structured questionnaire with eight respondents (pastry chef, CDP pastry, demi chef, commis, daily worker, trainee). Results showed the majority of respondents rated the selection of raw materials, control of kneading temperature, resting of dough, and number of laminations as “Good” to “Very Good,” although there is a need for improvement in the understanding of temperature control. The processing process includes ingredient preparation, dough making (gluten development, elasticity), lamination forming (folding and rolling with butter), dough shaping, proofing (final fermentation for volume), and baking, Presentation involves visual double check, test panel, as well as cleanliness of equipment for safety.